Himalayan Yew (Taxus wallichiana Zucc.) : a Multipurpose Rare Gymnosperm in India - Singh, Harish (Indian Forester, 2007)
The communication deals with taxonomy, vernacular names, botanical description, distribution, habitat and chromosome number along with economic uses viz. edible, medicinal, ethnomedicinal, poisonous, timber, wood, dye, fuel, fodder, incense, etc. of Taxus wallichiana Zucc. in India. An effort has also been made to describe the chemical constituents, present status, threats, propagation, conservation and management of this rare species in detail.